Pengaruh Variasi Bentuk Permukaan Piston dengan Campuran Bahan Bakar Ethanol Terhadap Emisi Gas CO dan HC pada Motor Bensin 100CC - Yulius Dicky Prasetya; Sugeng Hadi Susilo (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The high demand for motorised vehicles in Indonesia has resulted in an increased demand for fossil fuels, which has led to a decrease in their availability. One alternative solution is to utilise ethanol as fuel. The use of ethanol can increase the octane value of the fuel, but this requires adjustments to the engine's compression ratio. One way to increase the compression ratio is to modify the piston surface. By applying alternative fuels and modifying the piston surface, it is expected to reduce CO and HC exhaust emissions. This study aims to determine the effect of various piston surface shapes on CO and HC exhaust emissions when using pertalite and pertalite fuel mixture with ethanol. In this study, the test used a gas analyser to obtain CO and HC emission data. The research data is presented in tabular form and analysed using the two-way ANOVA method and graphs. The results of using variations in piston surface and fuel mixture showed the highest reduction in CO emissions of 65.9% at RPM 6000 and HC emissions of 48.5% at RPM 3500.